Design and Implementation of Music Website Based on Vue Framework Using AI Technologies - Ma, Yuan (Journal of Theory and Practice of Management Science, 2025)
This article briefly describes a music website designed and developed based on the Vue framework. The website refers to popular music websites and apps today, absorbs their advantages, and compensates for their disadvantages. It has a simple but personalized page, simple and convenient operation, complete functions, and high practicality, with the aim of facilitating listeners. This project is developed using the Vue.js framework and is a simple and easy-to-use music website. On this website, users can register, log in, modify personal information, listen to music, watch music videos, and collect their favorite songs, providing users with a comfortable experience.